Global survey on surgeon preference and current practice for pancreatic neck and body cancer with portomesenteric venous involvement - Ishida, Hiroyuki; Stoop, Thomas F.; Oba, Atsushi; Bachellier, Philippe; Ban, Daisuke; Endo, Itaru; Franklin, Oskar; Fujii, Tsutomu; Gulla, Aiste; Hackert, Thilo; Halimi, Asif; Hirano, Satoshi; et al. (HPB, 2025)
Background - Evidence regarding the optimal surgical approach for pancreatic neck/body cancer with portomesenteric vein (PV) involvement is scarce. We aimed to clarify the current practice using an international survey. - Methods - An online survey was distributed to members of nine international associations and study groups. Surgeons who performed pancreatectomy with PV resection (PVR) in the last 12 months were asked about three clinical scenarios with different PV involvement: scenarios A (<90°; length 1 cm), B (<90°; length 3 cm), and C (90-180°; length 3 cm), with or without common hepatic artery (CHA) involvement. PVR was defined according to the ISGPS definition. - Results - Overall, 222 surgeons from 49 countries in 6 continents completed the survey. The most selected procedures were left pancreatectomy with PVR ISGPS-type 1 for scenario A (52.3 %), PVR ISGPS-type 2 for B (28.8 %), and pancreatoduodenectomy with PVR ISGPS-type 3 for C (28.4 %). In patients with CHA involvement, the most selected procedures were left pancreatectomy without arterial reconstruction for A (57.7 %) and B (50.0 %), and total pancreatectomy for C (29.7 %). - Conclusions - The survey illustrates the heterogeneity in surgical management of pancreatic neck/body cancer with PV involvement, indicating the need for prospective studies and guidelines.